Financing Orphan Drugs Through a Blockchain-Supported Insurance Model - Ho, Lok Sang; Zhang, Tianle; Kwok, Tony Chun Tak; Wat, Kam Pui; Lai, Francisco T. T.; Li, Spencer (Frontiers in Blockchain, 2022)
The cost of treatment for rare diseases is notoriously high imposing threats to the global healthcare system. Existing market-based tools for orphan drugs are not designed to reduce drug prices and could be hampered by adverse selection. We propose an alternative insurance mechanism, Massive Group Insurance (MGI), which aims at reducing the prices of orphan drugs through offering separate Intellectual Property Right (IPR) Fees to the drug company from an MGI Agency, which will collect insurance premiums from each country on each orphan drug that the country wants all its citizens to enjoy access to. The premiums will be calculated so as to ensure that the drug company will collect a profit no smaller than what it enjoys under the traditional model. The plan uses the group insurance concept and will generate a significant increase in drug use. Blockchain technology is used to facilitate authentication and effective IPR payments and ensure data security and low administrative cost. This model can potentially be extended to other categories of expensive drugs and vaccines.